Determination of maximum tilt angle from analytic signal amplitude of magnetic data by the curvature-based method - Luan, Pham Thanh; Minh, Le Huy; Oksum, Erdinc; Thanh, Do Duc (Vietnam Journal of Earth Sciences, 2018)
Imaging buried geological boundaries is one of a major objective during the interpretation of magnetic field data in Geophysics. Therefore, edge detection and edge enhancement techniques assist a crucial role on this aim. Most of the existing edge detector methods require to obtain special points such as in general the maxima of the resulting image. One of the useful tools in estimating edges from magnetic data is the tilt angle of the analytical signal amplitude due to its value slightly dependence on the direction of magnetization. In this study, the maxima of the tilt angle of analytical signal amplitudes of the magnetic data was determined by a curvature-based method. The technique is based on fitting a quadratic surface over a 3×3 windows of the grid for locating any appropriate critical point that is near the centre of the window. The algorithm is built in Matlab environment. The feasibility of the algorithm is demonstrated in two cases of synthetic data as well as on real magnetic data from Tu Chinh-Vung May area. The source code is available from the authors on request.ReferencesAkpınar Z., Gürsoy H., Tatar O., Büyüksaraç A., Koçbulut F., Piper, JDA., 2016. Geophysical analysis of fault geometry and volcanic activity in the Erzincan Basin, Central Turkey, Complex evolution of a mature pull-apart basin. Journal of Asian Earth Sciences, 116, 97-114. Beiki M., 2010. Analytic signals of gravity gradient tensor and their application to estimate source location, Geophysics, 75(6), 159-174.Blakely R. J., and Simpson R.W., 1986. Approximating edges of source bodies from magnetic or gravity anomalies, Geophysics, 51, 1494-1498.Chen An-Guo, Zhou Tao-Fa, Liu Dong-Jia, Zhang Shu, 2017. Application of an enhanced theta-based filter for potential field edge detection: a case study of the LUZONG ORE DISTRICT, Chinese Journal of Geophysics, 60(2), 203-218.Cooper G.RJ., 2014. Reducing the dependence of the analytic signal amplitude of aeromagnetic data on the source vector direction, Geophysics, 79, 55-60.Cordell L., 1979. Gravimetric Expression of Graben Faulting in Santa Fe Country and theEspanola Basin, New Mexico. In Ingersoll, R.V., Ed., Guidebook to Santa Fe Country, New Mexico Geological Society, Socorro, 59-64.Cordell L and Grauch V.J.S., 1985. Mapping Basement Magnetization Zones from Aeromagnetic Data in the San Juan Basin, New Mexico, The Utility of Regional Gravity and Magnetic Anomaly Maps, Society of Exploration Geophysicists, Tulsa, 181-197.Hsu S.K., Coppense D., Shyu C.T., 1996. High- resolution detection of geologic boundaries from potential field anomalies: An enhanced analytic signal technique, Geophysics, 61, 1947-1957.Le D.C., Application of seismic exploration methods to identify geological structural characteristics supporting for hydrocarbon potential assessment in TuChinh - Vung May basin, Ph.D. Thesis, Hanoi University of Mining and Geology.Li X., 2006. Understanding 3D analytic signal amplitude: Geophysics, 71(2), 13-16.Miller H.G. and Singh V., 1994. Potential Field Tilt a New Concept for Location of Potential Field Sources, Journal of Applied Geophysics, 32, 213-217.Nabighian M.N., 1972. The analytic signal of two-dimensional magnetic bodies with polygonal cross-section: Its properties and use of automated anomaly interpretation, Geophysics, 37, 507-517.Nguyen N.T., Bui V.N., Nguyen T.T.H., 2014. Determining the depth to the magnetic basement and fault systems in Tu Chinh - Vung May area by magnetic data interpretation, Journal of Marine Science and Technology, 14(4a), 16-25.Nguyen X.H, San T.N, Bae W., Hoang M.C, 2014. Formation mechanism and petroleum system of tertiary sedimentary basins, offshore Vietnam, Energy Sources, Part A, 36,  1634-1649.Phillips J.D., Hansen R.O. and Blakely R.J., 2007. The use of curvature in potential-field interpretation, Exploration Geophysics, 38(2), 111-119.Rao D.B., and Babu N.R., 1991. A rapid method for three-dimensional modeling of magnetic anomalies, Geophysics, 56(11), 1729-1737.Roest W.R., Verhoef  J., and Pilkington M., 1992. Magnetic interpretation using the 3-D analytic signal, Geophysics, 57, 116-125.Tran N., 2017. Sediment geology of Vietnam, VNU Press.Tran T.D., Tran N., Nguyen T.H., Dinh X.T., Pham B.N., Nguyen T.T., Tran T.T.T.N., Nguyen T.H.T., 2018. The Miocenedepositional geological evolution of Phu Khanh, Nam Con Son and Tu Chinh - Vung May basins in Vietnam continental shelf, VNU Journal of Science: Earth and Environmental Sciences, 34(1), 112-135.Vo T.S., Le H.M., Luu V.H., 2005. Three-dimensional analytic signal method and its application in interpretation of aeromagnetic anomaly maps in the Tuan Giao region, Proceedings of the 4th geophysical scientific and technical conference of Vietnam, Publisher of Science and Engineering 2005.Wijns C, Perez C and Kowalczyk P, 2005, Theta map: Edge detection in magnetic data, Geophysics, 70, 39-43.